2014
DOI: 10.1021/ef5011995
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Scale Assessment of Nanoparticle-Stabilized CO2 Foam for Enhanced Oil Recovery

Abstract: In this paper, we evaluate nanoparticle-stabilized CO2 foam stability and effectiveness in enhanced oil recovery at the pore and micromodel scales. The nanoparticle-stabilized CO2 gas-in-brine foams maintain excellent stability within microconfined media and continue to be stable after 10 days, as compared to less than 1 day for surfactant foam. The nanoparticle-stabilized CO2 foams are shown to generate a 3-fold increase in oil recovery (an additional 15% initial oil in place), as compared to an otherwise sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(76 citation statements)
references
References 28 publications
2
71
0
Order By: Relevance
“…Nguyen et al [137] evaluated NP-stabilized CO2 foam stability and effectiveness in EOR of different types of oils (light, medium and heavy oils) at micromodel scales. All three oils showed substantial additional oil recovery and a potentially valuable reservoir homogenization effect because NP-stabilized CO2 foam flooding resulted in significantly smaller oil-in-water emulsions (Figure 16).…”
Section: Nano-assisted Gas Floodingmentioning
confidence: 99%
“…Nguyen et al [137] evaluated NP-stabilized CO2 foam stability and effectiveness in EOR of different types of oils (light, medium and heavy oils) at micromodel scales. All three oils showed substantial additional oil recovery and a potentially valuable reservoir homogenization effect because NP-stabilized CO2 foam flooding resulted in significantly smaller oil-in-water emulsions (Figure 16).…”
Section: Nano-assisted Gas Floodingmentioning
confidence: 99%
“…A closer look in the IR images showed that butane bubbles condensed in the mobile zone, and the condensation of butane bubbles would have brought high flow in this region. The high effectiveness of the C4-SAGD run is thought to be due to the combined effect of bubbles reducing the mobility of the penetrating fluid and reducing the viscous fingering phenomena [32], bubble condensation leading to fast flow in the mobile zone, and the dissolution of butane in bitumen. The pore scale analysis of the C4-SAGD showed a 3.19% recovery improvement over 5 seconds in the captured pore scale region as shown in Fig.…”
Section: B Pore Scale Analysismentioning
confidence: 99%
“…Polymer is the most commonly used stabilizer to keep foam stable; however, it is only suitable for low-temperature conditions of no higher than 90 • C because of heat degradation in polymers [30,31]. Nanoparticles are also very popular and effective stabilizers [32][33][34][35]. However, the poor dispersion ability of nanoparticles limits their application in high temperature and high salinity conditions.…”
Section: Introductionmentioning
confidence: 99%